Silymarin, the antioxidant component of Silybum marianum, prevents sepsis-induced acute lung and brain injury - VELİOĞLU ÖĞÜNÇ, AYLİZ; ERCAN, FERİHA; ŞENER, GÖKSEL; AKBAY, TUĞBA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2008)
Background. Sepsis is associated with enhanced generation of reactive oxygen species, which leads to multiple organ dysfunctions. Based on the potent antioxidant effects of silymarin, we investigated the putative protective role of silymarin against sepsis-induced oxidative damage in lung and brain tissues. Materials and methods. Sepsis was induced by cecal ligation and perforation (CLP). Sham and CLP groups received either vehicle or silymarin (50 mg/kg, p.o.) or 150 mg/kg i.p. N-acetylcysteine (NAC) for 10 days prior and immediately after the operation. Six hours after the surgery, rats were decapitated and blood was collected for the measurement of proinflammatory cytokines (tumor necrosis factor-alpha, interleukin-1 beta, and IL-6) levels, lactate dehydrogenase activity, and total antioxidant capacity. Lung and brain samples were taken for the measurement of malondialdehyde and glutathione levels, myeloperoxidase activity, thromboplastic activity, and also for histological assessment. Formation of reactive oxygen species in tissue samples was monitored by using chemiluminescence technique with luminol and lusigenin probe. Results. Sepsis increased serum TNF-alpha, IL-1 beta, IL-6 levels, and lactate dehydrogenase activity and decreased total antioxidant capacity. On the other hand, tissue glutathione levels were decreased while malondialdehyde levels and myeloperoxidase activity were increased in both the lung and the brain tissues due to CLP. Furthermore, luminol and lucigenin chemiluminescence were significantly increased in the CLP group, indicating the presence of the oxidative damage. Silymarine and NAC treatment reversed these biochemical parameters and preserved tissue morphology as evidenced by histological evaluation. Conclusions. Silymarin, like NAC, reduced sepsis-induced remote organ injury, at least in part, through its ability to balance oxidant-antioxidant status, to inhibit neutrophil. infiltration, and to regulate the release of inflammatory mediators. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: silybum marianum; silymarin; sepsis; antioxidant; cytokine; myeloperoxidase; glutathione; N-acetylcysteine; lung; brain; TISSUE FACTOR; MILK THISTLE; MOUSE SKIN; RAT-LIVER; MODEL; MYELOPEROXIDASE; COAGULATION; KINASE; KIDNEY; CELLS